Integrating Lean Startup and Educational Methodologies in the Development of the Sorghum Entrepreneur Marketplace - Noerhartati, Endang; Saurina, Nia (LifeSciFi, 2024)
This study explores the integration of lean startup and educational methodologies in developing the sorghum entrepreneur marketplace, aimed at empowering Small and Medium Enterprises (SMEs) within the sorghum industry in East Java. Leveraging the javelin board for idea validation and SWOT Analysis for strategic insights, the research outlines a systematic approach to marketplace creation, from initial design through to iterative development and refinement. Central to this process is the lean startup methodology, which facilitates rapid prototyping, feedback gathering, and learning to adapt to market needs efficiently. This approach not only expedites the development of the marketplace but also embeds a culture of innovation and continuous improvement among sorghum entrepreneurs. The findings underscore the importance of combining practical entrepreneurial tools with educational principles to enhance the competitiveness and sustainability of agricultural-based companies. This research contributes to the broader discourse on entrepreneurial education, highlighting the critical role of digital platforms in fostering innovation and resilience among SMEs in the agricultural sector.